USING COMIC STRIPS AS MEDIA OF TEACHING TO INCREASE THE NINTH GRADE STUDENTS’ ABILITY IN WRITING NARRATIVE TEXTS AT SMP YLPI MARPOYAN PROGRAM PLUS PEKANBARU - Yurrinda Yozi Prameshwari Yozi Prameshwari; Eliwarti '; Jismulatif ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This classroom action research aims at finding out how effective the use of comic strips in the process of learning English. Writing is a productive skill that is important to be learned at school. Yet, in the process of teaching writing the teacher rarely use appropriate, joyful, and effective media which make the students feel bored. The teacher should use interesting media to motivate the students. Hence, using comic strips as media of teaching can help the students to generate ideas and explore language in a creative way, especially in narrative texts. This research would answer the research question which has been stated : ‘Can the use of comic strips improve the ninth grade students’ ability in writing narrative texts?’. The sample of this research was the ninth grade students of SMP YLPI Marpoyan Program Plus Pekanbaru. The participants were 25 students (IX-2). This research was conducted in two cycles which consisted of eight meetings. The data were obtained through pre-test, post-test cycle 1, post-test cycle 2, and observation sheet for the students and the teacher. The results of this research showed good improvements in terms of students’ participation in teaching and learning process and the students’ writing ability. The Pre-Test score was 47,86 increased to 57,95 in Post-Test Cycle 1 and increased to 78,39 in Post-Test Cycle 2. The students’ activities were also increased from 52,8% in cycle 1 to 85,2% in Cycle 2. In conclusion, comic strips could be used as media of teaching writing narrative texts to increased the students’ writing ability. Comic strips could help the students to generate ideas and also could motivate the students to follow the lesson.   Keywords: Comic Strips, Media, Writing, Narrative Text